Islamic Work Ethic and Public Sector Innovation: Challenges and Solutions - Usman, Muliati; Mat, Norsiah (International Business Education Journal, 2021)
In a fast-moving modern era with many moral problems, Islamic work ethic (IWE) has been a pivotal concept in the success of innovation in the public sector. The perfection of “Akhlaq” is a major priority of the IWE. Its principles contain virtues derived from the Qur’an and Hadith. Practising these values will provide benefits for both individuals as well as society. Thus, Muslim who embed the values of IWE directly in their work will have more innovative behaviour. However, the value of  IWE is not easy to be implemented to support innovation in the public sector. The concept of IWE  is not easily accepted and applied by Islamic workers, even though they understand and know that these values are derived from the Qur’an. This situation is further worsened in a problematic public sector environment and culture. Therefore, the purpose of this study is to clarify the significant relationship between IWE and innovation in the public sector by identifying factors or aspects to solve the challenge in the public sector.  This concept paper found that there are still inconsistent findings on the impact of IWE on innovation. Specifically, a comprehensive concept of  IWE is absolutely needed to ensure that innovation will be more easily achieved in anticipating challenges in the public sector. Thus, this study contributes by providing a model of the relationship between IWE and innovation in the public sector.